2018
DOI: 10.1002/chem.201800862
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Controlled Simultaneous “On Demand” Release of Cytotoxic Combinations for Bimodal Killing of Cancer Cells

Abstract: In this contribution, we report a novel entirely photocontrolled nanoplatform comprising a binary mixture of pluronic copolymers capable of self-assembling into core-shell micelles and co-entrapping two photoactivatable components: a benzoporphyrin photosensitizer for photodynamic therapy (PDT) and coumarin-photocaged chemotherapeutic agent Chlorambucil (CAB). The resulting supramolecular micellar assembly is about 30 nm in diameter with a polydispersity index <0.1, stable for more than 72 h, and exhibits exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Under these experimental conditions the cmc is 0.0030 % and the resulting micelles show a diameter ca. 30 nm . NBF‐NO has very low solubility in pure water but effectively dissolves upon encapsulation in the Pluronic ® micelles as confirmed by its typical absorption band with maximum at 385 nm ( a in Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Under these experimental conditions the cmc is 0.0030 % and the resulting micelles show a diameter ca. 30 nm . NBF‐NO has very low solubility in pure water but effectively dissolves upon encapsulation in the Pluronic ® micelles as confirmed by its typical absorption band with maximum at 385 nm ( a in Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Tessaro et al [ 88 ] reported a novel photocontrolled nanoplatform comprising two photoresponsive components—a benzochlorin PS ( Figure 25 a) for PDT and a coumarin-photocaged chlorambucil (compound 50 , Figure 25 b)—into core-shell micelles to amplify the anticancer activity against MCF-7 human breast adenocarcinoma cells. The authors demonstrated that with simultaneous irradiation with visible light in the micelles, benzochlorin produces 1 O 2 as a PS and compound 50 acts as a prodrug by leaving of PPG group ( Figure 25 b).…”
Section: Porphyrins Combining Photocleavage Systems and Some Applicat...mentioning
confidence: 99%
“… Benzochlorin used as a PS for PDT ( a ) and coumarin-photocaged (compound 50 ) release chlorambucil ( b ) [ 88 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The emission maximum of pq complexes 3a,b underwent a much smaller blueshift upon cooling to 77 K, whichi sp ossibly the result of ap redominant 3 IL (p!p * ,NN and N^C) character in the emissive states of these complexes. Due to limited solubility of these POSS complexes in water,c ommercially availablet riblock copolymer Pluronic F-127 (PF127)w as employed as ap olymeric matrix [14] for the photophysical measurementsi na queous solution. Surprisingly,t he luminescence quantum yields of complexes 1a and 2a in aqueouss olution containing 0.05 %P F127 were higher than those in organic solvents.T his abnormal phenomenon can be attributed to the fact that the large and rigid POSS core facilitatedthe formation of nanoaggregates by complexes 1a and 2a in aqueous solution, which suppressedi ntramolecular rotation and hence promoted radiative decay.A lthough complex 3a also has aP OSS scaffold, it wasm ore solubilized in PF127-containing aqueous solution.T hus, it appears that the polarity of solvents plays a more important role in the emission behavior of this complex, that is, higher emission intensity in less polar solvents.…”
Section: Electronicabsorption and Emission Propertiesmentioning
confidence: 99%